Hookworms Make Us Human: The Microbiome, Eco‐immunology, and a Probiotic Turn in Western Health Care. (1st March 2019) - Lorimer, Jamie
Abstract: Historians of science have identified an ecological turn underway in immunology, driven by the mapping of the human microbiome and wider environmentalist anxieties. A figure is emerging of the human as a holobiont, composed of microbes and threatened by both microbial excess and microbial absence. Antimicrobial approaches to germ warfare are being supplemented by probiotic approaches to restoring microbial life. This article examines the political ecology of this probiotic turn in Western health care. It focuses on Necator americanus—a species of human hookworm—and its relations with immunologists. The analysis moves from a history of human disentanglement from hookworm, to contemporary anxieties about their absence. It examines the reintroduction of worms for helminthic therapy and explores emerging trajectories for probiotic health care involving the synthesis, modification, and/or restoration of worms and their salutary ecologies. The conclusion differentiates these trajectories and identifies an emerging model of "post‐paleo" microbiopolitics.